TINJAUAN MASLAHAH TERHADAP PRAKTIK PEMBERIAN NAFKAH SUAMI DALAM PERNIKAHAN SIRI (Studi Kasus pada Alumni Pesantren di Kecamatan Bumiayu, Kabupaten Brebes) - Fauzi, Muhammad Farkhan; Syawaludin; Takdir Hardani La ajiri (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study discusses the practice of providing alimony by husbands in serial marriages carried out by three couples of Islamic boarding school alumni in Bumiayu District, Brebes Regency. Although their marriage has not been officially recorded by the state, they remain committed to fulfilling their obligation to provide for their wives in the form of birth and mental support. This study aims to analyze the practice through a normative approach with maslahah theory, in order to see the extent to which the fulfillment of the sustenance reflects the benefits from an Islamic perspective. The method used is qualitative which is descriptive-analytical. The approach used in this study is normative using maslahah theory.  Primary data were generated from interviews with three married couples in series about alimony practices and secondary data from related literature. The results of the study show that the practice of providing sustenance has included aspects of maslahah daruriyah and tahsiniyah, but has not fully fulfilled the maslahah hajiyah, especially in the provision of housing. Judging from the existence of the evidence in maslahah shows that this practice is not entirely in line with the principle of the benefit of Islamic law because it is carried out in the context of marriage that is not recognized by the state which can cause harm, especially to the wife. In addition, in some postulates mention the need to announce his marriage. Thus, this practice is categorized as maslahah al-mulghah, which is a benefit based on individual prejudice.